STUDY ON CLINICAL FEATURES AND IMAGE CHARACTERISTICS OF PATIENTS WITH ACUTE PULMONARY EMBOLISM AT CAN THO CENTRAL GENERAL HOSPITAL IN 2021-2023 - Huynh, Anh Khoa; Bui, Ngoc Thuan; Doan, Dung Tien; Pham, Thi Anh Thu (Cantho Journal of Medicine and Pharmacy, 2023)
Background: Acute pulmonary embolism is a common acute cardiovascular syndrome. Accurate and timely diagnosis to initiate treatment is very important, helping to reduce mortality and morbidity rates. Objectives: To decribe the clinical and imaging characteristics of patients with acute pulmonary embolism at Can Tho Central General Hospital in 2021-2023. Materials and methods: A prospective, descriptive cross-sectional study was conducted on 55 patients with acute pulmonary embolism at Can Tho Central General Hospital in 2021-2023. Results: The mean age was 65.3 ± 11.4, the male/female ratio was 1/1.6. The most common clinical symptom was dyspnea (81.8%), tachypnea (60%). All the cases where the D-dimer test was performed showed a D-dimer (+) result. Normal chest radiograph results accounted for 32.7%. On echocardiography, signs of right ventricular dilatation accounted for 36.4%. Deep vein thrombosis of the lower extremities and proximal deep vein thrombosis account for a high proportion (69.1% and 65.5%). Acute pulmonary embolism occurs more frequently on the right side than on the left side (92.7% vs 74.5%), in the lower lobe branches more often than in the upper and middle lobe branches (87.3% right, 67.3% left). Conclusions: Acute pulmonary embolism had diverse clinical symptoms. Computed tomography of the pulmonary artery was an imaging technique that plays an important role in the diagnosis. Acute pulmonary embolism occured more often on the right side than on the left, and more often in the inferior lobe branches than in the superior and middle lobe branches.